Pengaruh Kualitas Jasa Terhadap Kepuasan Pelanggan Pada Pusat Terapi Anak Kita - zahra zakaria (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2022)
In general, in Indonesia, autism is not yet known clearly by everyone because not everyone has the ability to detect the symptoms of this disorder. This study aims to determine how the quality of services in our child's therapy center and what is actually expected by the customer or parents who have children with autism, and what has been perceived by customers to the quality of services received. The number of samples contained in this study are as many as 23 respondents of customers in our Child Autism Therapy Center, with a purposive random sampling technique. The research instruments were arranged in the form of questionnaires / questionnaires using the Likert's scale. The results revealed that with dk - | and the level of error set is 545 and compared with the price of F table, it turns out that F count is greater than t table (17,891 »3.49). there is a strong and significant relationship between service quality and customer satisfaction with our Child Autism Therapy Center, this shows that the quality of services has a considerable contribution to customer satisfaction, which then becomes one of the important factors in the marketing of service companies, thus expected the managers of service companies can always pay attention to the quality of services they provide to customers. So that there is evidence of compatibility between expectations that are perceived by the customer and the real services they obtain.